Altered interhemispheric functional connectivity in end-stage renal disease patients receiving hemodialysis without cognitive impairment - Xue, Yan; Li, Bo; Qian, Shaowen; Sun, Gang; Jia, Fengyu; Liu, Kai (Frontiers in Neurology, 2025)
BackgroundPrevious studies have shown that alterations in brain structure, metabolism, and function are prevalent in patients with end-stage renal disease (ESRD); however, the synchronization of early functional changes between the two functional hemispheres in these patients remains unclear. This study aimed to analyze interhemispheric functional connectivity in patients with ESRD using resting-state fMRI with voxel mirrored homotopic connectivity (VMHC) algorithm.MethodsThe study cohort comprised 36 patients with ESRD receiving hemodialysis without cognitive impairment and 34 matched healthy control (HCs). All participants completed neuropsychological assessments (e.g., Mini-Mental State Examination, Montreal Cognitive Assessment, Self-Rated Anxiety Scale, and Self-Rated Depression Scale) prior to MR scanning, and all patients underwent laboratory tests.ResultsCompared with HCs, patients with ESRD exhibited significantly decreased VMHC values in bilateral regions including the inferior parietal lobule/angular gyrus, superior temporal gyrus, insula, precentral gyrus, middle occipital gyrus, calcarine/cuneus, and lingual gyrus. No brain regions showed increased VMHC values. Although patients with ESRD had no clinically significant cognitive impairment, their performance on neuropsychological tests was significantly worse than that of HCs (all p =0.001). Notably, no correlations were observed between VMHC values and neuropsychological test scores or clinical indicators in patients with ESRD (all p > 0.05).ConclusionOur findings suggest that interhemispheric connectivity is impaired in patients with ESRD without cognitive impairment, providing novel insights into early-stage neural abnormalities in this population.